2019
DOI: 10.35940/ijeat.a3030.109119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shroud Hole on the Force Characteristics of a Circular Cylinder

M.F. Osrin*,
A.M. Azmi*,
H. Yusoff
et al.

Abstract: Characteristics of flow pass a shrouded cylinder were investigated experimentally using uniform and non-uniform hole shrouds. The experiments were performed to compare the effect of hole-uniformity of the perforated shroud on the cylinder lift and drag. The porosity for uniform hole shrouds in triangular and square configurations were set around 0.30, while that for non-uniform hole shrouds were set from 0.25 to 0.37. The diameter ratio between the shroud and the bare cylinder was set at 2.0. The experiment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…They discovered that a shrouded cylinder reduced the vortex-induced oscillating lift forces. Experiments conducted by Osrin et al, [10] on the effect of shroud hole uniformity on a circular cylinder wake showed that, although all shrouded cylinder models reduced drag significantly in comparison to that of the bare cylinder case, the non-uniform hole shrouds were considerably effective than those of uniform hole shrouds. Misman et al, [11] discovered that simply changing the slot profile can prevent vortex shedding along the structure's length and wake vortices' formation.…”
Section: Introductionmentioning
confidence: 94%
“…They discovered that a shrouded cylinder reduced the vortex-induced oscillating lift forces. Experiments conducted by Osrin et al, [10] on the effect of shroud hole uniformity on a circular cylinder wake showed that, although all shrouded cylinder models reduced drag significantly in comparison to that of the bare cylinder case, the non-uniform hole shrouds were considerably effective than those of uniform hole shrouds. Misman et al, [11] discovered that simply changing the slot profile can prevent vortex shedding along the structure's length and wake vortices' formation.…”
Section: Introductionmentioning
confidence: 94%
“…According to their results, the use of a special device reduced the scour depth around the pier. Osrin et al (2019) experimentally investigated the flow pattern past the shrouded cylinder. Their work revealed the impact of perforated shrouds' uniform and non-uniform holes on the cylinder's drag and lift coefficients.…”
Section: Introductionmentioning
confidence: 99%